Religion and Technology: Reinterpreting Marx’s Opium of the People - Losianus Harjon (Politeknik Siber Cerdika Internasional, 2026)
This study aims to analyze the relevance of Karl Marx’s concept of religion as the “opium of the people” in the context of contemporary technological development. The research is motivated by the ambivalent role of religion in modern society, where the advancement of science and technology simultaneously strengthens rationality while also generating existential crises and a loss of meaning. This study employs a qualitative approach with a library research method, focusing on critical analysis of Marx’s philosophical texts and their relevance to current social phenomena. The findings indicate that religion possesses an ambivalent function: it serves as a source of psychological comfort and existential stability, yet it can also function as an ideological mechanism that obscures social reality and hinders transformation. In the digital era, the “opium” function of religion finds its parallel in technology, which similarly operates as a means of escaping human suffering. Nevertheless, this study argues that religion cannot be reduced to mere illusion, as it continues to play a significant role as a source of values, reflection, and social transformation.